Opportunities and Challenges for Using Augmented Reality-Based Learning Media in Learning Chemistry in The Era of Society 5.0 - Akbar, Jakub Saddam; Djakariah, Djakariah (Cognitive Development Journal, 2023)
This research aims to explore the use of augmented reality (AR) in the context of chemistry learning with a descriptive qualitative approach. Through in-depth analysis of a number of literature sources, including scientific articles, books, and related publications, this research identifies the opportunities and challenges associated with the integration of AR in chemistry learning. One of the main focuses is on the potential of AR in improving students' understanding of abstract chemistry concepts. The results of this literature study highlight the important role of AR in providing a more interactive learning experience, clarifying difficult-to-understand chemistry concepts, and the challenges in developing and integrating this technology into educational curricula. The implications of these findings can provide guidance for educational institutions to effectively adopt AR in chemistry learning.